Experimental Study on Mechanical Properties of Lime-Basalt Fiber Modified Red Mudstone Filler - XIAO Pan; LIN Pengjie; CHEN Nan; WANG Wen; LIU Jia; LIU Xianfeng (工程科学与技术)
Red mudstone accounts for more than 25% of the total area in southwest China. With the continuous development of high-speed railway construction in southwest China, a large amount of waste slag will inevitably be produced, and its growth rate may accelerate with the increase of construction activities. utilizing the red mudstone waste residue for high-speed railway subgrade not only reduces costs but also realize resource reuse and environmental protection. Lime modified red mudstone has been verified to be fill material of high-speed railway subgrade. Lime modification could significantly enhance the strength and water stability of red mudstone filler(RM) but also increases its brittleness. To mitigate this, basalt fibers are incorporated, which could effectively reduce the brittleness of the lime modified red mudstone filler(LMRM).This study focuses on the mechanical properties analysis of lime-basalt fiber modified red mudstone filler(LFMRM). Specifically, direct shear tests were conducted on samples with varying basalt fiber contents ( 0%, 0.1%, 0.2%, 0.3%, 0.4% ) to elucidate the effects on shear strength, dilatancy, and brittleness, under that the lime content was fixed at 4%, and the compaction degree reached 95% ( dry density was 1.67 g/cm3 ),in 7 days maintenance. Additionally, the modification mechanism of lime-basalt fiber modified red mudstone filler was revealed via scanning electron microscope(SEM).The results indicate strain softening behavior in the stress-displacement curves for lime-basalt fiber modified red mudstone filler and the shear strength of lime modified red mudstone increases after adding fiber (Fig.4). The peak and residual shear strength of lime-basalt fiber modified red mudstone with fiber content of 0.1% -0.4% is larger than that of lime modified red mudstone. Because the fiber is evenly distributed in the soil, the friction and cementation force between the fiber and the soil will increase its peak stress. After reaching the peak strength, the specimen is destroyed and cracks are generated. The bridge effect of the internal fiber can effectively inhibit the deformation of the soil and increase the residual stress. When the content of basalt fiber is 0% -0.4%, the peak cohesion is greater than the residual cohesion, the peak internal friction angle is less than the residual internal friction angle. A fiber content of 0.2% is identified as optimal (Fig.9), maximizing cohesion and internal friction angle. At a fiber content of 0.2%, cohesion and internal friction angle reach their peak values, identifying this as the optimal content. At this level, the peak cohesion and residual cohesion are 1.1 and 1.2 times higher, respectively, than those of lime modified red mudstone filler, and 1.8 and 1.5 times higher than those of modified with basalt fiber alone. Similarly, the peak internal friction angle and residual internal friction angle are 1.2 and 1.1 times greater than those of lime modified red mudstone filler, and both are 1.1 times higher than those of modified with basalt fiber alone. These findings underscore the significant synergistic effect of basalt fiber and lime in improving soil strength. The brittleness index diminishes with increasing vertical stress and remains considerably lower than that of lime modified red mudstone filler, highlighting the fibers' role in brittleness reduction. Moreover, in the semi-logarithmic coordinates, dilatancy angles reduce linearly with increasing vertical stress, with fiber modified samples exhibiting lower angles than their lime-only counterparts. This is due to when the dense inclusions formed by fiber and lime soil are sheared, the fiber restricts the displacement and dilatancy, thus enhancing the residual strength, reducing the brittleness index and the dilatancy angle, furthermore, the three-dimensional grid structure woven by fibers is restrained by each other, which further reduces the brittleness index and the dilatancy angle. Besides, the relationship between brittleness index and dilatancy angle can be divided into two stages, corresponding to two different shear behaviors: softening-dilatancy and softening-shrinkage (Fig.14). The fitting formula indicate that there is a correlation between the dilatancy angle and the brittleness index. Specifically, the fibers constrain soil, decreasing the dilatancy angle, and the brittleness index decreases with the the dilatancy angle.As for the microscale investigation, the fiber-lime synergistic improvement of red mudstone filler mainly includes three aspects:1 Hydration reaction occurs between lime and soil, through cation exchange, hydration reaction and pozzolanic reaction with the mineral composition of red mudstone filler, lime generates calcium hydroxide, calcium carbonate, hydrated calcium silicate, hydrated calcium aluminate (CAH), hydrated calcium aluminosilicate (CASH) and other hydrates (Fig.14). These hydrates fill the micropores and attach to the aggregates and fibers surface, thus forming a denser soil structure, enhancing interfacial friction, and improving the strength and restraining the deformation of the soil;2 When the dense lime-fiber soil inclusions are sheared, the stretching and drawing of the fibers effectively inhibit the soil displacement and enhance the soil strength;3 The resultant three-dimensional network formed by the fibers significantly improves soil integrity, enabling the lime and fiber combination to effectively limit soil deformation. These insights are invaluable for the design and improvement of red mudstone filler in high-speed railway subgrade applications in southwest China, providing a strategic approach to enhancing subgrade stability under varied loading conditions.